Follower Status: Forms and Strategies of Mass Movements toward Controversial Social Concepts of Protest Activism - Katasila, Suriyasai; Santiboon, Toansakul T. (Journal of Ecohumanism, 2024)
To investigate and analyze the status of the followers who attended the People’s Alliance for Democracy (PAD) in 2005–2009; the United Front for Democracy Against Dictatorship (UDD) in 2006–2010; and the People’s Democratic Reform Committee (PDRC) in 2013-2014 under their thinking that the right to freedom of peaceful assembly is a basic human right. As characterized by the model of Hersey and Blanchard, was guided by the leaders’ status. The concept of followership characteristics and styles were followed and compared. Adapting the 24-item Follower Creative Thinking on Participating Protest Rally (FCTPPR) in four scales through 600 followers were assessed. The FCTPPR is valid and reliable. It was found that Thai-style followers are thought leaders with independence, and have the capital potential within society. Simply put, the masses were ready for themselves and didn’t intend to advance or lead in supporting the rallying groups of followers. The followers’ minds have been reflected in their thoughts on the leadership in the participating group and being followers of their leadership. Significant differences in the followers’ perceptions of their four creative thinking abilities in attending the parts of the PAD, UDD, and PDRC mass movement rally protest groups were also found.